Problem-Solving Trends in Management Science - Prasad, S. Benjamin (Management Science, 1966)
The purpose of this paper is to present data and some interpretation relating to (a) the classes of problems in general, (b) as they relate to specific business functional areas, and (c) the management science techniques employed to solve the problems. The presentation is based upon a content analysis of 354 articles published in Management Science, January 1955 through September 1964, upon the classes of O. R. problems suggested by Professor Russell Ackoff in his Manager's Guide to Operations Research. Data presented in this analysis suggest that the majority of problems were those concerned with allocation in the production functional area and that linear programming was the most widely used technique. At the end of the paper it is suggested that “management science” is still evolving, and has a long way to go if it should emerge as a science concerned with (top) managerial problems in industrialized and developing countries.